Is low-volume high intensity interval training a time-efficient strategy for improving body composition and cardiovascular health in children and adolescents? Evidence from a systematic review and three-level meta-analysis - Zheng, Weihua; Xing, Yue; Yin, Mingyue; Guo, Yan; Piao, Shunzhe; Cao, Yang; Chen, Hongbo; Li, Hansen (Frontiers in Physiology, 2025)
ObjectivesThis meta-analysis assessed the impact of low-volume high-intensity interval training (LV-HIIT) on body composition and cardiovascular health in children and adolescents, while examining potential moderating factors.MethodsA systematic search was conducted in PubMed, Web of Science, the Cochrane Library (CENTRAL), and CNKI from inception to April 2025. A three-level random-effects model was used to estimate the overall effects, and subgroup analyses supplemented with meta-regression were performed to explore potential moderators and sources of heterogeneity.ResultsA total of 23 studies (996 participants, including 246 females) were included, with 6 studies on normal-weight and 17 on overweight/obese individuals. Compared with controls, low-volume high-intensity interval training (LV-HIIT) significantly reduced BMI (g = −1.24), fat mass (g = −0.99), body fat (g = −0.89), waistline (g = −0.42), weight (g = −0.34), and SBP (g = −0.37), while improving VO2max (g = 1.35). No significant differences were observed versus MICT. Subgroup and dose-response regressions suggested that weight status, age, intervention duration, training frequency, repetitions, and per-repetition time may alter the observed effects. Descriptive findings indicated comparable effects of LV-HIIT with small-sided games and sprint interval training but greater benefits over moderate-intensity interval trainingConclusionLV-HIIT can effectively and time-efficiently improve body composition and cardiovascular health in children and adolescents, with overall effects comparable to MICT. Exercise prescriptions should carefully consider weight status, age, and intervention characteristics; however, given the limited number of studies and potential bias, the conclusions should be interpreted with caution. Limited descriptive comparisons indicate that LV-HIIT produces effects similar to SSG and SIT, and may offer greater benefits than MIIT.Systematic Review Registrationhttps://osf.io/exhjm/.